Reducing Anchorage in Ports: Changing Technologies, Opportunities and Challenges - Heaver, Trevor D. (Frontiers in Future Transportation, 2021)
Developments in digitisation and the need to reduce carbon emissions have increased attention on port call optimisation. Just-in-time arrival for ships is recognised in the literature as being achieved more readily in container trades than in bulk trades. This paper examines the governance and trade logistics conditions in the bulk trades of Vancouver, Canada, as the increasing number of ships at anchor gives rise to the need to explore what is done elsewhere to manage the incidence of anchorage. Newcastle, Australia, is used to identify critical governance and logistics factors that played a role in the development of innovative practices to reduce anchorage.